Policy of Sustainable Growth: Local People Perception in the Regional Economic Development of Iskandar in Malaysia - Rabe, Noor Suzilawati; Mohamed Osman, Mariana; Bachok, Syahriah (American Scientific Publishers, 2017)
Iskandar Malaysia development is one of the latest regional economic development established in Malaysia. There are five flagship zones proposed under the implementation of Iskandar Malaysia within the boundary of Johor Bahru and Pontian district. This paper intends to discuss the implementation concept of sustainable growth in Iskandar Malaysia. The research hoped that the findings of the study would help to improve the planning of regional economic development in Malaysia in achieving sustainable development principles.